Change in the Teaching of Economics in Russia due to the Fall of the Soviet Union (Papeles, 2019)
In the course of the last two decades of the twentieth century the Soviet Union went through great changes in its political structure, but, above all, economic changes. The set of economic reforms that began to be implemented in 1985 completely altered the thinking of the Russians and, in addition, had a great impact on the way in which the economy was taught in the universities of this nation. This research work aims to show the changes in thinking about the profession of the economist in the Soviet Union and what the changes were in the programmatic contents of Russian universities due to Perestroika and the fracture of the Union. It also aims to show the impact of the two processes mentioned earlier in the history of Russia’s most influential economics faculty: the one of Moscow State University.
Keywords: reforms; teaching of economics; Perestroika; Soviet Union